2019
DOI: 10.1073/pnas.1819156116
|View full text |Cite
|
Sign up to set email alerts
|

SHARPIN at the nexus of integrin, immune, and inflammatory signaling in human platelets

Abstract: Platelets mediate primary hemostasis, and recent work has emphasized platelet participation in immunity and inflammation. The function of the platelet-specific integrin αIIbβ3 as a fibrinogen receptor in hemostasis is well defined, but the roles of αIIbβ3 or integrin-associated proteins in nonhemostatic platelet functions are poorly understood. Here we show that human platelets express the integrin-associated protein SHARPIN with functional consequences. In leukocytes, SHARPIN interacts with integrin α cytopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 49 publications
(60 reference statements)
1
27
2
Order By: Relevance
“…In addition, αIIbβ3 (or GPIIb/IIIA) and C‐type lectin‐like receptor 2 (CLEC‐2) are involved in ubiquitination‐dependent modulation of platelet function. The αIIbβ3‐associated protein SHARPIN induces ubiquitination and activation of NF‐κB proteins via the linear ubiquitin chain assembly complex (LUBAC) and the E3 ligases HOIP and HOIL‐1 after platelet stimulation with thrombin or inflammatory agonists . Another E3 ubiquitin ligase, RN181, was shown to interact with platelet integrin αIIbβ3 suggesting a further link between integrin signal transduction and ubiquitination .…”
Section: Identification Of E3 Ubiquitin Ligases In Plateletsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, αIIbβ3 (or GPIIb/IIIA) and C‐type lectin‐like receptor 2 (CLEC‐2) are involved in ubiquitination‐dependent modulation of platelet function. The αIIbβ3‐associated protein SHARPIN induces ubiquitination and activation of NF‐κB proteins via the linear ubiquitin chain assembly complex (LUBAC) and the E3 ligases HOIP and HOIL‐1 after platelet stimulation with thrombin or inflammatory agonists . Another E3 ubiquitin ligase, RN181, was shown to interact with platelet integrin αIIbβ3 suggesting a further link between integrin signal transduction and ubiquitination .…”
Section: Identification Of E3 Ubiquitin Ligases In Plateletsmentioning
confidence: 99%
“…Here activation is accomplished by ubiquitination of the NF‐κB‐inhibitor IκBα and its subsequent degradation by the proteasome complex (Figure ) . The proteasome is also relevant for modulating the signaling pathways of αIIbβ3, GPVI, and CLEC‐2 (Figure ) and might play a pivotal role in additional signaling pathways in platelets . In this review, we summarize the known fundamental regulatory mechanisms and functional aspects of the proteasome in human platelets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HSCs commit and differentiate into MKs, which then mature in a process that is characterized by increased ploidy. Mature MKs release platelets after remarkable morphologic changes, which require a profound rearrangement of the cytoskeleton . Previous studies, including our own work, have revealed that various factors, primarily the specific cytokine thrombopoietin (TPO), can directly promote platelet production by acting at different stages through the extracellular signal‐regulated kinase 1/2 (ERK1/2) and Akt signaling pathways .…”
Section: Introductionmentioning
confidence: 99%
“…Mature MKs release platelets after remarkable morphologic changes, which require a profound rearrangement of the cytoskeleton. 1,2 Previous studies, including our own work, have revealed that various factors, primarily the specific cytokine thrombopoietin (TPO), can directly promote platelet production by acting at different stages through the extracellular signal-regulated kinase 1/2 (ERK1/2) and Akt signaling pathways. [3][4][5] In addition, some factors may also indirectly facilitate platelet production through TPO, which is suggested by the data that approximately 60% of TPO in circulation is controlled by the platelet glycoprotein Ibα (GPIbα).…”
Section: Introductionmentioning
confidence: 99%